Victim of Robberies Becomes Suspect: Indonesian Criminal Law and Human Rights Perspective - Ahmad Fahmi Ilham Mulloh; Muhammad Rafif Wibowo; Adilla Putri Diva (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
A young man from East Nusa Tenggara had to experience the crime of being a victim of a robbery, but unfortunately, he was named a suspect for killing the robber to defend himself. In the Indonesian legal basis, citizens have the right to defend themselves, protect and feel safe from the threat of fear, but what happened to the youth is contrary to this legal basis. The purpose of this research is to analyze the reasons why victims of robbery are named suspects with the aim of defending themselves from the perspective of Indonesian criminal law and human rights. The author also relates the decision to the existing laws and regulations, is the decision relevant to the law or not? This research adopts the normative legal research method. The results of this research are to provide new information regarding the right action and how to defend oneself according to the law if experiencing a similar criminal event. The findings of the research show that victims of robbery can take evasion actions by seeking self-protection from the authorities or by running away for their own safety, and according to the law, murder is a criminal act so that the victim can be made a suspect but there are other considerations